A Study on Basics of Chromatographic Techniques: Exploring the Fundamental Principles and Applications of Chromatographic Techniques in Protein Purification (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Chromatography is an important biophysical technique that requires qualitative and quantitative research to isolate, classify and purify components from the mixture. Proteins may be cleaned based on properties, such as size and form, total load, hydrophobic surface groups and stationary binding ability. The mechchanisms for ion exchange, surface adsorption, partition and exclusion of size utilizing four molecular separation techniques. The stationary platform, including boards, thin layers and paper chromatography, is the foundation for other chromatographic technology. Chromatography in columns is one of the most popular processes of purification of proteins.